Case Report: Parvovirus B19 infection complicated by hemophagocytic lymphohistiocytosis in a heart-lung transplant patient - Zhang, Xuewu; Wang, Jingxia; Huang, Xiaohan; Zhu, Yue; Zhu, Yijing; Tang, Lingling; Cai, Hongliu; Fang, Xueling; Huang, Lingtong (Frontiers in Immunology, 2023)
Immunosuppressed patients can contract parvovirus B19, and some may experience hemophagocytic lymphohistiocytosis (HLH). Herein, we describe the first report of hemophagocytic lymphohistiocytosis in a heart-lung transplant patient with concomitant parvovirus B19 infection. The patient was treated with intravenous immune globulin (IVIG) and the features of HLH were remission. This instance emphasizes the significance of parvovirus B19 monitoring in transplant patients with anemia; if HLH complicates the situation, IVIG may be an adequate remedy. Finally, a summary of the development in diagnosing and managing parvovirus B19 infection complicated by HLH is provided.